Cibercultura na formação docente: memórias, narrativas e experiências em tempos de pandemia. - MOREIRA, Judith Anteles (2023)
In this work I report my academic trajectory focusing on the curricular activities carried out through the Digital Technologies in Network. The methodology used in this research was inspired by writing to assemble my narrative, that is, the memories and initial experiences and collective discoveries throughout the course of graduation, in the period from 2018 to 2023. The narrated experiences were extracted from conversations of WhatsApp groups and activities posted on the google classron platform. I conclude that the knowledge and experiences with the use of these digital technologies, even if in a limited way, allowed me to believe that in addition to plural spaces and places, these educational networks also contribute to our teacher training.